JAK 2 MUTATION IN RECURRENT FETAL LOSS - Irshad, Romana; Farooq, Umer; Haroon, Zeeshan; Malik, Saqib (Journal of Ayub Medical College Abbottabad, 2019)
Background: The frequency of recurrent fetal loss (RFL) is around 1% of the total pregnancy. Workup is recommended in patients after three consecutive fetal losses. A multitude of chromosomal, environmental, structural immunological and hematological factors can result in RFL. Frequency of pregnancy loss is increased in MPD patients carrying JAK2 V617F mutation. In fact, JAK2 mutation is an independent risk factor for pregnancy complication and fetal loss. This study was conducted to assess the role of the JAK 2 mutation in recurrent pregnancy loss. Methods: This was a case control study conducted in Armed Forces Institute of Pathology, Rawalpindi. Using un-matched case-control situation a sample size of 216 cases and 216 controls was calculated using the WHO sample size calculator with assumption of 95% confidence interval, 1:1 ratio of cases to control, expected proportion of mutation as 0.10% and 1.06% in control and cases respectively. DNA analysis were performed and results were recorded done by kit method. The data was entered and analyzed using SPSS version 18.0. Odds ratio was calculated to assess the association between JAK2 V617F mutation and recurrent fetal loss. Results: Three out of 216 cases were positive for JAK 2 mutation while one control had positive JAK 2 mutation. The prevalence of JAK2 mutation in cases of RFL was 1.38% (95% C.I 0.58-2.17%).The odds ratio for JAK 2 mutation in cases and controls was 3.028 (95% C.I of 0.28-76.13) and a P-value of 0.623. Conclusion: JAK2 positive females are 3.03 times more at risk of having RFL as compared to JAK2 negative pregnant females. JAK2 mutation testing may be recommended for inclusion in the workup to manage RFL Keywords: Recurrent Fetal Loss; JAK 2 mutation, JAK 2, Abortion